MEDAN MAKNA KATA “TAJATUAH” - Sucy Kurnia Wati (Jurnal Elektronik WACANA ETNIK, 2017)
This paper aims to analyze and describe the field of meaning of the word “tajatuah”. Data are analyzed using the matching method and the method used.It can be concluded that the words that include the field of meaning of the word “tajatuah” are “tumbang, tagolek, tarambau, taguliang, taserak, tajungkek, tadorong, talapeh, tasungkua, rabah, balambin, taampeh, taambua, badabuak, taduduak, tasanduang, tatungkai, tatunggik , tasialia, tajilapak, tapaleset, tagalincia, tajirangkang, tataruang, tatilantang, tagurajai, tatungkuik, luruah, roboh, rontok, runtuah, tabantiang, tabuang, tacampak, lareh” and “taambuang”. It can be concluded, the word “tajatuah” includes the types of lexical meanings, contextual meanings, associative meanings, idiomatic meanings, and proverbs. Based on the classification of the field of tajatuah there are (1) the basic meaning and additional meaning, (2) the value of taste, (3) the prevalence of usage and (4) the distribution.